MEDIASI VARIABEL KREDIBILITAS MEREK DALAM MENGANALISIS PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP EVALUASI MEREK: Sebuah Studi Kasus Pada Pengguna Smartphone Samsung di Kota Medan - Silaban, Pantas H.; Silalahi, Andri Dayarana K. (Jurnal Manajemen dan Bisnis, 2021)
This study aimed to examined the effect of Electronic Word-Of-Mouth on Samsung brand evaluation moderated brand credibility. The population in this study is infinite numberwhich contained by all the people who are using the Samsung products in Medan. The number of samples used in this study are 100 respondents with technique of determining the sample is purposive random sampling with judgment sampling method that researchers use certain criteria that will be used as a sample in this study. The type of research used in this study is the type of causality research. The independent variable in this research is electronic word-of-mouth, and the dependent variable is the brand evaluation and the moderation/intervening variable is brand credibility. The results showed that partially electronic word-of-mouth has a positive and significant effect on brand credibility, electronic word-of-mouth have positive and significant effect on brand evaluation, brand credibility has a positive and significant impact on brand evaluation, electronic word-of- mouth has a positive and significant influence on brand evaluation with brand credibility as a moderating variable. In addition, the results of this study also indicate that there is an indirect effect of the more dominant electronic word-of-mouth on brand evaluation through brand credibility is 0.529. The conclusion in this research is E-WOM not directly against Samsung brand evaluation in Medan. Suggestions for further research are to add more independent variables and use SEM analysis tools with more objectives in research objectives and targets.